Factors Influencing Organizational Commitment of Employees in BCEL Bank: A Case Study of Oudomxay Branch - Bouangeun, dath; Hoongsengpha, Soudtida; Sengchanh, souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objectives of this research were to study the organizational commiment of employees in BCEL bank, to study the most important factor of employee organizational commitment and to study the factors influencing organizational commitment of employees in BCEL Bank: A case study of Oudomxay Branch, the research was conducted by using a questionnaire as an instrument for collecting data from 46 staffs in BCEL bank at Oudomxay branch. The Cronbach alpha reliability coefficient was 0.908 and IOC was higher than 0.6, the statistics used for data analysis were frequency, percentage, mean, standard deviation and Multiple Regression analysis. The results revealed that: 1) The organizational commitment of the Banque pourle commerce exterieur Lao publice employees that in overall the organizational commitment was at highest level. In this, the employee to keep staff in organizations and operations in the organization, the desire to stay in the organization and independence in the organization was intended to stay at high level. 2) The most important factor of employee organizational commitment was included: the compensation, leadership, the job advancement expectation, the attitudes toward colleagues and the career development respectively. 3) The factors effecting organization commiment of employees at BCEL banks at Oudomxay branch findings revealed that: the career development factor, the leadership factor and the compensation factors. There was a relationship in the same direction and affected towards the organizational commitment at the statistical significance level of 0.05.